A New 3D 10-Connected Cd(II) Based MOF With Mixed Ligands: A Dual Photoluminescent Sensor for Nitroaroamatics and Ferric Ion - Wang, Jun; Wu, Jian; Lu, Lu; Xu, Hongjia; Trivedi, Manoj; Kumar, Abhinav; Liu, Jianqiang; Zheng, Mingbin (Frontiers in Chemistry, 2019)
The precise unification of functional groups and photoluminescence properties can give rise to MOFs that can offer diverse applications like selective detection of nitroaromatic compounds (NACs) which are considered to be an important ingredient of explosive as well as cation and anion sensing. Hence, a new 3D metal-organic framework (MOF) [Cd2(btc)(bib)(HCOO)(H2O)·H2O]n (1) has been synthesized using mixed ligand strategy by solvothermal reaction of cadmium acetate with two ligands viz. 1,3,5-benzenetricarboxylic acid (H3btc) and 1,4-bis(2-methyl-imidazol-1-yl)butane (bib). The MOF 1 possesses highly 10-connected network which is based on Cd4(btc)2(bib)4 molecular building block. The studies showed that 1 could be taken as the fluorescent sensor for sensitive recognition of NACs, in particular 2,4,6-trinitrophenol (TNP) with notable quenching (Ksv = 5.42 × 104 M−1) and LOD of 1.77 ppm. Additionally, 1 also displayed selective sensing for Fe3+ ions with Ksv = 6.05 × 103 M− 1 and LOD = 1.56 ppm. Also, this dual sensor displayed excellent reusability toward the detection of TNP and Fe3+ ion. Theoretical calculations have been performed to propose the probable mechanism for the sensing luminescence intensity. Calculations indicated that because of the charge transfer and weak interaction that is operating between NACs and MOF, the weakening in the photoluminescence intensity resulted.